PENINGKATAN KUALITAS PENDIDIKAN DI PERGURUAN TINGGI MELALUI TOTAL QUALITY MANAGEMENT (TQM) DALAM MENYONGSONG MASYARAKAT EKONOMI ASEAN (MEA) - Aprina Chintya (Pascasarjana IAIN Metro, 2016)
Total Quality Management (TQM) is an effort done by college to improve their management quality in achieving the goals. TQM related to quality system consist of planning system quality, controlling system quality, and improving system quality. Hence, in this research, the researcher manages to explain the improving education quality at Collage through TQM in welcoming MEA. This is descriptive literature review research. The source of the data is taken from books and others review related to improving education quality at Collage through TQM. This research employs documentation as data collection technique and content analysis to analyze the data which use the procedure to make the conclusion. The result shows that when TQM applied at collage continuity and consistently, the quality of graduates will increase, in this case they are capable to compete in industry field.